2005
DOI: 10.1001/archinte.165.10.1192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Metabolic Syndrome on Hospital Outcomes in Acute Myocardial Infarction

Abstract: In an unselected population of patients with AMI, the prevalence of metabolic syndrome was high. Metabolic syndrome appeared associated with worse in-hospital outcome, with a higher risk of development of severe heart failure. Among metabolic syndrome components, hyperglycemia was the main correlate of the risk of development of severe heart failure during AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
96
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 44 publications
9
96
3
5
Order By: Relevance
“…However, comparable and representative data regarding the prevalence of MetS in the setting of acute MI and the effect of MetS on the long-term prognosis is lacking in Turkish patients. In this single-center study, the prevalence of MetS on admission was 42.6% in patients hospitalized with acute MI, a finding consistent with previous studies that showed a higher prevalence of MetS in patients with acute MI [10][11][12].…”
Section: Months After Acute Myocardial Infarctionsupporting
confidence: 91%
“…However, comparable and representative data regarding the prevalence of MetS in the setting of acute MI and the effect of MetS on the long-term prognosis is lacking in Turkish patients. In this single-center study, the prevalence of MetS on admission was 42.6% in patients hospitalized with acute MI, a finding consistent with previous studies that showed a higher prevalence of MetS in patients with acute MI [10][11][12].…”
Section: Months After Acute Myocardial Infarctionsupporting
confidence: 91%
“…5 MetS is associated with a larger coronary infarct size, severe heart failure, and higher overall in-hospital complications, including acute renal failure. 6,7 MetS has also been demonstrated to amplify vascular wall thickness and stiffness 8 and create an overall pro-thrombotic state. 9 Patients with MetS exhibit impaired fibrinolysis through increased plasminogen activator-1 levels compared with those without MetS.…”
mentioning
confidence: 99%
“…11,12 Zeller et al 13 reported that acute MI in patients with MetS was associated with worse in-hospital outcomes and a higher risk of developing severe heart failure. In patients with manifest vascular disease, the presence of MetS is associated with advanced vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratios of people with 1 and greater than or equal to 2 MetS component disorders were 2.69 and 4.30, respectively. 13,15 Although many reports suggest that MetS is likely to be a risk factor for stroke, only a few included patients with AINS. 16,17 In these studies, MetS was associated with an increased risk of AINS in elderly people (age .…”
Section: Years Of Follow-up Of 3453 Adults (Age $ 20 Years) In the Camentioning
confidence: 99%